Accountability in times of exception: an exploratory study of account-giving practices during the early stages of the COVID-19 pandemic in Italy. Issue 4 (1st March 2021) - Andreaus, Michele; Rinaldi, Leonardo; Pesci, Caterina; Girardi, Andrea
Abstract : Purpose: The purpose of this paper is to explore the role of accountability in times of exception. The Italian government's account-giving practices are critically analysed with respect to the distinct modes in which duties of accountability are discharged for the exceptional measures taken during the early stages of the COVID-19 pandemic outbreak in early 2020. Design/methodology/approach: This paper draws on an exploratory case study. The case analysis draws primarily on data obtained through publicly available documents and covers the period between January 1 and August 7, 2020. Findings: The paper reveals that the Italian government employed various accountability styles (rebuttal, dismissal, reactive, proactive and coactive). Each style influenced both how the government justified its conduct and how it sought to form distinctive relationships with social actors. Originality/value: The paper uses the notion of "styles of accountability" to empirically illustrate how an unprecedented public governance challenge can reveal broader accountability trends. The paper contributes to accountability research by elucidating how governments tackle ambiguity and uncertainty in their systems of public accountability in extraordinary times.